Helminth infection alters IgE responses to allergens structurally related to parasite proteins - Santiago, Helton da Costa (J Immunol, 2014)
Immunological cross-reactivity between environmental allergens and helminth proteins has been demonstrated, though the clinically-related implications of this cross-reactivity have not been addressed. To investigate the impact of molecular similarity among allergens and cross-reactive homologous helminth proteins in IgE-based serologic assessment of allergic disorders in helminth-infected population, we performed Immunocap™ tests in filarial-infected and non-infected individuals for IgE measurements to allergen extracts that contained proteins with high levels of homology with helminth proteins and IgE against representative recombinant allergens with and without helminth homologues were performed. The impact of helminth infection on the levels and function of the IgE to these specific homologous and non-homologous allergens was corroborated in an animal model. We found that having a tissue-invasive filarial infection increased the serological prevalence of Immunocap™ identified IgE directed against house dust mite and cockroach, but not against timothy grass, the latter with few allergens with homologues in helminth infection. IgE ELISA confirmed that filaria-infected individuals had higher IgE prevalences to those recombinant allergens that had homologues in helminths. Mice infected with helminth Heligmosomoides polygyrus displayed increased levels of IgE and positive skin tests to allergens with homologues in the parasite. These results show that cross-reactivity among allergens and helminth proteins can have practical implications altering serologic approaches to allergen testing and brings a new perspective to the Hygiene Hypothesis.